BRIDGING GLOBAL AND LOCAL VALUES IN AN INTERNATIONAL EFL CURRICULUM: EXPLORING STUDENTS’ COMMUNICATIVE COMPETENCE AND IDENTITY FORMATION - Nanik Ratnawati; Nunung Nurjati; Endah Yulia Rahayu (Premise: Journal of English Education and Applied Linguistics, 2026)
This study investigates how the integration of global and local values within an international English as a Foreign Language (EFL) curriculum supports students’ communicative competence and identity negotiation. A qualitative case study was conducted involving 20 Grade 7 students and three teachers at a private Islamic junior high school in Surabaya, Indonesia. Multiple datasets were generated through a 20-item questionnaire, semi-structured interviews, classroom observations, and curriculum document analysis. The questionnaire dataset was analyzed descriptively using frequencies, percentages, means, and standard deviations, while interview, observation, and document data were analyzed using thematic analysis. The findings indicate that global and local values were integrated across classroom interaction, learning materials, and instructional practices, creating opportunities for students to develop communicative competence while maintaining their local cultural identity. Rather than experiencing identity conflict, students negotiated their identities positively by combining global perspectives with pride in their Indonesian cultural values. This study contributes to EFL research by demonstrating that the integration of global and local values serves as a contextual mechanism linking communicative competence and identity negotiation within an international curriculum. The findings also provide practical implications for designing culturally responsive international EFL curricula that simultaneously promote global competence and local cultural sustainability.